6y+14=-7-y

Simple and best practice solution for 6y+14=-7-y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6y+14=-7-y equation:


Simplifying
6y + 14 = -7 + -1y

Reorder the terms:
14 + 6y = -7 + -1y

Solving
14 + 6y = -7 + -1y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add 'y' to each side of the equation.
14 + 6y + y = -7 + -1y + y

Combine like terms: 6y + y = 7y
14 + 7y = -7 + -1y + y

Combine like terms: -1y + y = 0
14 + 7y = -7 + 0
14 + 7y = -7

Add '-14' to each side of the equation.
14 + -14 + 7y = -7 + -14

Combine like terms: 14 + -14 = 0
0 + 7y = -7 + -14
7y = -7 + -14

Combine like terms: -7 + -14 = -21
7y = -21

Divide each side by '7'.
y = -3

Simplifying
y = -3

See similar equations:

| 11-3(x-1)=6+x | | 4(4x-3)-6x=x | | 3-2x(x+1)=x-2 | | -x+4x+1=3x-1+2 | | -2x+2x+4=3x-2x+2 | | 6-8x-3=-39+6x-14 | | 80+x=180 | | -9(x-7)-6=57 | | -20-9b+1=16b+20 | | 2(6x+5)=3x-26 | | 3-19p=-18p+20 | | -6w-12+2w=28 | | (10/3)/(2/21) | | -4/-5y=72 | | -3m=-6-5m | | 52/650 | | (1/4x-6)=(2/3x+3) | | 4u=3u-8 | | 2[3x-(4x-8)]=5(x-8) | | 3x+15=11+5x | | -7x+16=8(5x+2) | | -8p=176 | | 4(x+2)/6 | | 3+5(-8a-1)=-6-(3a-4) | | 0.15-0.01(x+1)=-0.03(2-x) | | (-2x/11)=66 | | 7x+3=2(3x+1)-x+8 | | x+6=15-x | | 13/6+x=6 | | 16n^2-8n-15=0 | | 2x-5y=4x+15 | | 5/2x=3/2x-4 |

Equations solver categories